EFEKTIFITAS ASI EKSKLUSIF PADA PERKEMBANGAN MOTORIK KASAR BAYI DI SYAMTALIRA ARON, ACEH UTARA - Melati Julizar; Muslim Muslim (JOMIS (Journal of Midwifery Science), 2021)
Exclusive breastfeeding coverage in Indonesia has not reached the expected rate, which is around 80%. Exclusive breastfeeding is very important for the baby's growth and development. Babies who are exclusively breastfed and with good nutritional status have normal gross motor development. Breastfeeding exclusively supports infant growth, improves brain cell development, language development, and motor development of babies because breast milk contains various nutrients that can promote growth and brain development. This study aims to analyze the effectiveness of exclusive breastfeeding on the gross motor development of infants in Syamtalira Aron, Aceh Utara. This study used a comparative design with a cross sectional approach. The number of research respondents was 92 respondents, with a total sampling technique. Exclusive breastfeeding data and gross motor development were collected using a questionnaire. In this study, it is known that the frequency distribution of exclusive breastfeeding is 37 people (37.5%), and 55 people (62.5%) are not exclusively breastfed. Data analysis used the Mann Whitney U. The results of the bivariable study showed that the exclusive breastfeeding group had a minimum value of 7 and a maximum value of 10. While the non-ASI group had a median value of 7 with a minimum value of 6 and a maximum of 10, the average ranking of the Exclusive breastfeeding group was 66.50 higher than the non-ASI group with a value of 33.05 and a p-value of 0.000. From the results of this study, it can be concluded that exclusive breastfeeding is better than non-exclusive breastfeeding for infants aged 0-6 months for infant development. Thus, parents are expected to pay more attention to their children in exclusive breastfeeding for 0-6 months of the baby's gross motor development.